Processing method of antistatic high temperature and high pressure resistant polymer cushion
By using high-temperature composite technology to process polymer buffer pads, the shortcomings of materials such as kraft paper and aramid fiber in the existing technology under high temperature and high pressure conditions are solved, and anti-static and high temperature and high pressure polymer buffer pads are realized, satisfying printing The demand for circuit board making in the use of high-frequency circuit substrates.
Patent Information
- Application Number
- CN202410704798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-03
AI Technical Summary
In the prior art, kraft paper, as a buffer pad, has problems such as moisture absorption, unenvironmental protection, poor heat resistance, short life, high cost and poor buffering under high temperature and high pressure conditions, and cannot meet the problems of printed circuit boards in the use of high-frequency circuit substrates. Require. At the same time, aramid fiber and fluoroelastic materials also have insufficient temperature resistance, material hardening, and electrostatic problems under high temperature and high pressure.
The processing method of an anti-static, high temperature and high pressure-resistant polymer buffer pad is adopted, including at least one temperature-resistant bottom layer, at least one temperature-resistant surface layer, and at least one expansion layer arranged between the temperature-resistant surface layer and the temperature-resistant bottom layer, These layers of materials are superimposed and processed into polymer buffer pads through high-temperature composite technology.
The polymer buffer pad can quickly separate from the steel plate under high temperature and high pressure conditions, avoid deformation, delamination, internal deflation and other phenomena, and improve conductivity, reduce electrostatic adsorption, extend service life, reduce costs, and meet the needs of high-frequency circuit substrates Processing requirements.
Smart Images

Figure CN118721943B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of buffer pads, in particular to a processing method of an antistatic, high temperature and high pressure resistant polymer buffer pad. Background Art
[0002] The multi-layer circuit board (PCB & CCL) pressing plate is a process that uses the vacuum, high temperature and high pressure of the press to heat and cure the semi-cured sheet, and bond one or more inner layer etched boards and copper foils into a multi-layer board. During the pressing process, steel plates need to be placed on the upper and lower sides of the circuit board to ensure the flatness, uniformity, electrical and mechanical properties of the multi-layer circuit board. However, due to the hard material of the steel plate, the flow and coating of the semi-cured sheet resin of the multi-layer circuit board will be affected during pressing. Therefore, a buffer pad needs to be placed between the steel plate and the hot plate of the press so that uniform and controllable heating and buffer coating can be achieved during hot pressing of the multi-layer circuit board. In the current manufacturing process, multiple layers of kraft paper are generally placed to achieve this.
[0003] However, in the process of hot pressing, kraft paper as a buffer pad will have the following problems:
[0004] 1. Kraft paper is easy to absorb moisture during storage or transportation, which causes the kraft paper to stick to the steel plate during hot pressing;
[0005] 2. Kraft paper is not environmentally friendly, pulp production causes serious pollution, pulp requirements are high, and consumption is large;
[0006] 3. Kraft paper has poor heat resistance, short life and high cost. In the hot pressing process, the ordinary pressing temperature requires about 220℃, and the high temperature pressing temperature requires about 380℃. Kraft paper can only withstand a temperature of about 220℃, and it has aged and deteriorated after 4 hours × 4 times, and cannot be recycled for a long time, resulting in very high cost of kraft paper;
[0007] 4. Kraft paper has a high hardness and poor buffering properties under vacuum and high pressure conditions, and cannot improve the quality problems such as lack of glue, wrinkles, shrinkage, etc. that occur when laminating multi-layer circuit boards;
[0008] 5. When using multiple sheets of kraft paper, manual replacement is often required, requiring two people to work every day, and automation cannot be achieved.
[0009] Therefore, it is necessary to develop low expansion and contraction polymer cushioning pads for printed circuit boards.
[0010] If aramid fiber and fluororubber materials from home and abroad are used as cushions, the following problems may occur during the hot pressing process:
[0011] 1. Aramid fiber and fluororubber materials as cushions can be used for a long time at 250°C and for a short time at 300°C, which cannot meet the processing requirements of PTFE / hydrocarbon resin / LCP liquid crystal polymer / PPE / PPO materials used as high-frequency circuit substrates in microwave / micrometer wave fields. Among these materials, asbestos fiber has a cushioning property, which can withstand temperatures between 300 and 400°C and can be used repeatedly for a long time. However, asbestos is a type of carcinogen that can cause diseases such as asbestosis and pleural mesothelioma. Many countries have chosen to completely ban the use of this dangerous substance;
[0012] 2. Aramid fiber and fluororubber materials become harder and thinner after long-term use under vacuum and high pressure, losing their initial cushioning and thickness. The thermal resistance coefficient of the material changes, resulting in a change in the heating rate, and they cannot be used repeatedly for a long time.
[0013] 3. The surface coating of the fluororubber material buffer pad is PTFE material, which has a negative charge. When used with a steel plate in a vacuum and high temperature, a large amount of static electricity is generated. The surface of the buffer pad will absorb foreign matter, PP powder, etc., resulting in surface depressions, line gaps, open circuits and other quality risks on the circuit board;
[0014] Moreover, printed circuit board materials are constantly innovating and iterating, so it is necessary to develop anti-static, high-temperature and high-pressure resistant polymer buffer pads in the printed circuit board lamination process. Summary of the invention
[0015] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a processing method for an antistatic, high temperature and high pressure resistant polymer cushion, which enables the cushion to be quickly separated from the steel plate when pressed, without causing deformation, delamination, internal collapse and the like; and improves the conductive performance.
[0016] To achieve the above object, the present invention adopts the following technical solution:
[0017] A method for processing an antistatic, high temperature and high pressure resistant polymer cushion, the polymer cushion comprising at least one temperature resistant bottom layer, at least one temperature resistant surface layer and at least one expanded layer arranged between the temperature resistant surface layer and the temperature resistant bottom layer, when the expanded layer is more than two layers, each expanded layer is connected by at least one adhesive layer, the processing steps of the polymer cushion are as follows:
[0018] (1) Preparation of medicine: according to the formula components of the medicine required for the material treatment of the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer, the raw materials are respectively measured and prepared to obtain several kinds of material treatment medicines, and various material treatment medicines are added to the processing equipment of the corresponding layer materials for standby use. When the expanded layer has more than two layers, the material treatment medicines need to be prepared according to the formula components of the medicine required for the material treatment of the adhesive layer for standby use;
[0019] (2) preparing a heat-resistant bottom layer: taking a first grey cloth, performing a surface high-temperature pretreatment on the first grey cloth, and then using at least two material treatment solutions in step (1) to dip-coat the first grey cloth respectively, performing a heating treatment after each dipping treatment, and then rolling up to obtain a heat-resistant bottom layer for standby use;
[0020] (3) preparing a heat-resistant surface layer: taking a second grey cloth, applying a material treatment solution in step (1) to at least one side of the second grey cloth, and then drying and rolling the second grey cloth in a stepwise heating manner to obtain a heat-resistant surface layer for later use;
[0021] (4) Making a bulked layer: taking a third grey cloth, performing a surface high-temperature pretreatment on the third grey cloth, and then using at least three material treatment solutions in step (1) to dip-coat the third grey cloth respectively, performing a heating treatment after each dip-coating treatment, and then rolling up to obtain a bulked layer for standby use;
[0022] (5) Material roll packing machine: the material rolls of the heat-resistant bottom layer of step (2), the heat-resistant surface layer of step (3), and the expanded layer of step (4) are respectively arranged at the unloading end of the equipment, and the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer are aligned and stacked according to the structural order of the polymer cushion. When the expanded layer is more than two layers, at least one adhesive layer is also required to be arranged at the unloading end, and the adhesive layer is arranged between the two expanded layers. Subsequently, one end of each stacked layer of material is passed through the composite part of the processing equipment through the first traction part of the processing equipment, and pre-installed on the second traction part of the processing equipment;
[0023] (6) Material compounding: starting the processing equipment, and using the first traction part and the second traction part of the processing equipment to pull the layers of materials stacked in step (5) from the feed end of the compounding part to the processing area of the compounding part at a fixed length, and perform high-temperature compounding to obtain a strip-shaped polymer buffer material;
[0024] (7) Material cutting: The processing equipment transports the polymer cushioning material of step (6) to the cutting part of the processing equipment at a fixed length through the second traction part, and the polymer cushioning material is cut by the cutting part to obtain a polymer cushioning pad;
[0025] When the expanded layer has more than two layers, an adhesive layer needs to be prepared: take the fourth grey cloth, perform high-temperature surface pretreatment on the fourth grey cloth, and then use at least two material treatment solutions in step (1) to dip-coat the fourth grey cloth respectively. After each dipping treatment, it needs to be heated and then rolled up to obtain the adhesive layer.
[0026] Furthermore, the material treatment solution in step (1) includes an antistatic, wear-resistant and heat-resistant solution, a first bonding enhancement solution, a second bonding enhancement solution, a third bonding enhancement solution and a buffering and rebound enhancement solution.
[0027] Furthermore, the antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight:
[0028] Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%;
[0029] The first binding enhancement liquid contains the following components by weight:
[0030] Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%;
[0031] The second binding enhancement liquid contains the following components by weight:
[0032] Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%;
[0033] The third binding enhancement liquid contains the following components by weight:
[0034] Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%;
[0035] The buffering and rebound enhancing liquid contains the following components by weight:
[0036] Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%.
[0037] Among them, the material treatment solutions of the antistatic, wear-resistant and heat-resistant solution, the first bonding enhancement solution, the second bonding enhancement solution, the third bonding enhancement solution and the buffering rebound enhancement solution need to be mixed in a blender at high speed for 30 to 60 minutes at a stirring speed of 1200 to 1450 r / min, and then left to stand for more than 4 hours to obtain the product after taking each raw material according to the weight portion of each material treatment solution.
[0038] Furthermore, in the step (2), the surface of the first grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, each high-temperature impurity removal time is 30-60 minutes respectively; secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with a first bonding enhancement liquid, each dip-coating time is 30-60 minutes respectively; then, at least two high-temperature dryings are carried out at a high temperature of 300-400°C, each high-temperature drying time is 30-60 minutes respectively; then, the dried first grey cloth is subjected to two dip-coating treatments with a second bonding enhancement liquid, each dip-coating time is 30-60 minutes respectively; finally, at least two high-temperature dryings are carried out at a high temperature of 250-350°C, each high-temperature drying time is 30-60 minutes respectively, to obtain a heat-resistant bottom layer, which is then rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; and the dip-coating treatment adopts a dip coater.
[0039] Furthermore, in the step (3), an antistatic, wear-resistant and heat-resistant liquid medicine is evenly scraped on one side of the second grey cloth, and the scraping thickness is 0.3 to 0.31 mm. Subsequently, the second grey cloth is dried at 140°C, 170 to 190°C, 200°C to 250°C and 300°C to 350°C in sequence to obtain a temperature-resistant surface layer, and then the temperature-resistant surface layer is rolled up for standby use, wherein the drying is performed at 140°C for 3 to 10 minutes, at 170 to 190°C for 5 to 10 minutes, at 200°C to 250°C for 30 to 40 minutes, and at 300°C to 350°C for 30 to 40 minutes.
[0040] Furthermore, in the step (4), the surface of the third grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400° C., and the time for each high-temperature impurity removal is 30 to 60 minutes. Then, the third grey cloth after impurity removal is subjected to at least two dip coating treatments with the first bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. Then, the third grey cloth is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400° C., and the high-temperature drying time is 30 to 60 minutes. Then, the third grey cloth after drying is subjected to two dip coating treatments with the buffering rebound enhancement liquid, and the dip coating time is 30 to 60 minutes. The third grey cloth is dried for a second time at a temperature of 300-400°C for 30-60 minutes respectively, and then the third grey cloth is dried for a second time with a third bonding strengthening solution, and the dipping time is 30-60 minutes respectively, and then the third grey cloth is dried for a second time with a third bonding strengthening solution, and the dipping time is 30-60 minutes respectively, and then the third grey cloth is dried for a second time at a temperature of 250-350°C for a second time, and the high temperature drying time is 30-60 minutes respectively, to obtain a bulked layer, and then the bulked layer is rolled up for standby use; wherein, the high temperature impurity removal or high temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dipping machine.
[0041] Furthermore, in step (6), a laminating machine is used to perform high-temperature lamination on the stacked layers of materials, the laminating temperature is 360-400°C, the laminating time is 100-300 seconds, and the laminating pressure is 5-15 kg / cm 2 .
[0042] Furthermore, when making the bonding layer, the surface of the fourth grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and each high-temperature impurity removal time is 30-60 minutes. Secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with a first bonding enhancement liquid, and the dipping time is 30-60 minutes. Then, the first grey cloth is subjected to at least two high-temperature drying at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes. Then, the fourth grey cloth after drying is subjected to at least two dip-coating treatments with a second bonding enhancement liquid, and the dipping time is 30-60 minutes. Then, the fourth grey cloth is subjected to at least two high-temperature drying at a high temperature of 250-350°C, and the high-temperature drying time is 30-60 minutes. The bonding layer is then rolled up for standby use. The high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace, and the dipping treatment adopts a dip coater.
[0043] The beneficial effects of the present invention are as follows:
[0044] 1. The surface coating has very good release effect at high and low temperature. It can be quickly separated from the steel plate during pressing, and the release effect is better than that of PTFE coating.
[0045] 2. The temperature resistance of the surface coating (260 degrees to 380 degrees) is better than that of PTFE coating (260 degrees);
[0046] 3. The wear resistance of the surface coating is better than that of PTFE coating, and will not cause deformation, delamination, internal shrinkage, etc.
[0047] 4. Anti-static amount ≤10 8 At the same time, the conductivity can be improved and the adsorption of PP powder and dust can be reduced according to customer requirements and product characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a flow chart of the dip coating process of the present invention.
[0049] Figure 2 It is a composite flow chart of each material layer of the present invention.
[0050] Figure 3 It is a schematic diagram of the cushioning capacity test principle of the polymer cushion of the present invention.
[0051] Figure 4 It is a comparison chart of the "before pressing" and "rebound rate" of the polymer cushion of the present invention after each pressing number.
[0052] Figure 5 This is a graph showing the change in cushioning capacity of the polymer cushion of the present invention after various pressing times.
[0053] Figure 6 It is a temperature variation diagram of the polymer cushion and other buffer materials of the present invention.
[0054] Figure 7 This is a graph showing the temperature rise rate changes of the polymer cushion and other buffer materials of the present invention after various pressing times.
[0055] Figure 8 This is a graph showing the thickness variation of the polymer cushion and other buffer materials of the present invention after various pressing times.
[0056] Fig. 9 This is a comparison diagram of the expansion and contraction changes of the polymer cushion of the present invention and other buffer materials after being pressed together. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific embodiments and accompanying drawings:
[0058] like Figure 1-9 As shown, the present invention relates to a processing method of an antistatic high temperature and high pressure resistant polymer cushion, wherein the polymer cushion comprises at least one temperature resistant bottom layer, at least one temperature resistant surface layer, and at least one expanded body layer disposed between the temperature resistant surface layer and the temperature resistant bottom layer. When the expanded body layer is two or more layers, each expanded body layer is connected by at least one adhesive layer. The processing steps of the polymer cushion are as follows:
[0059] (1) Preparation of medicine: according to the formula components of the medicine required for the material treatment of the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer, the raw materials are respectively measured and prepared to obtain several kinds of material treatment medicines, and various material treatment medicines are added to the processing equipment of the corresponding layer materials for standby use. When the expanded layer has more than two layers, the material treatment medicines need to be prepared according to the formula components of the medicine required for the material treatment of the adhesive layer for standby use;
[0060] (2) preparing a heat-resistant bottom layer: taking a first grey cloth, performing a surface high-temperature pretreatment on the first grey cloth, and then using at least two material treatment solutions in step (1) to dip-coat the first grey cloth respectively, performing a heating treatment after each dipping treatment, and then rolling up to obtain a heat-resistant bottom layer for standby use;
[0061] (3) preparing a heat-resistant surface layer: taking a second grey cloth, applying a material treatment solution in step (1) to at least one side of the second grey cloth, and then drying and rolling the second grey cloth in a stepwise heating manner to obtain a heat-resistant surface layer for later use;
[0062] (4) Making a bulked layer: taking a third grey cloth, performing a surface high-temperature pretreatment on the third grey cloth, and then using at least three material treatment solutions in step (1) to dip-coat the third grey cloth respectively, performing a heating treatment after each dip-coating treatment, and then rolling up to obtain a bulked layer for standby use;
[0063] (5) Material roll packing machine: the material rolls of the heat-resistant bottom layer of step (2), the heat-resistant surface layer of step (3), and the expanded layer of step (4) are respectively arranged at the unloading end of the equipment, and the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer are aligned and stacked according to the structural order of the polymer cushion. When the expanded layer is more than two layers, at least one adhesive layer is also required to be arranged at the unloading end, and the adhesive layer is arranged between the two expanded layers. Subsequently, one end of each stacked layer of material is passed through the composite part of the processing equipment through the first traction part of the processing equipment, and pre-installed on the second traction part of the processing equipment;
[0064] (6) Material compounding: starting the processing equipment, and using the first traction part and the second traction part of the processing equipment to pull the layers of materials stacked in step (5) from the feed end of the compounding part to the processing area of the compounding part at a fixed length, and perform high-temperature compounding to obtain a strip-shaped polymer buffer material;
[0065] (7) Material cutting: The processing equipment transports the polymer cushioning material of step (6) to the cutting part of the processing equipment at a fixed length through the second traction part, and the polymer cushioning material is cut by the cutting part to obtain a polymer cushioning pad;
[0066] When the expanded layer has more than two layers, an adhesive layer needs to be prepared: take the fourth grey cloth, perform high-temperature surface pretreatment on the fourth grey cloth, and then use at least two material treatment solutions in step (1) to dip-coat the fourth grey cloth respectively. After each dipping treatment, it needs to be heated and then rolled up to obtain the adhesive layer.
[0067] Furthermore, the material treatment solution in step (1) includes an antistatic, wear-resistant and heat-resistant solution, a first bonding enhancement solution, a second bonding enhancement solution, a third bonding enhancement solution and a buffering and rebound enhancement solution.
[0068] Furthermore, the antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight:
[0069] Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%;
[0070] The first binding enhancement liquid contains the following components by weight:
[0071] Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%;
[0072] The second binding enhancement liquid contains the following components by weight:
[0073] Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%;
[0074] The third binding enhancement liquid contains the following components by weight:
[0075] Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%;
[0076] The buffering and rebound enhancing liquid contains the following components by weight:
[0077] Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%.
[0078] Among them, it should be noted that the material treatment liquids of the antistatic, wear-resistant and heat-resistant liquid, the first bonding enhancement liquid, the second bonding enhancement liquid, the third bonding enhancement liquid and the buffering and rebound enhancement liquid, after taking each raw material according to the weight of each material treatment liquid, need to be stirred and mixed at high speed in a blender for 30 to 60 minutes, and the stirring speed is 1200 to 1450r / min, so that the raw materials of each material treatment liquid are fully stirred to improve the dispersion uniformity; especially the antistatic, wear-resistant and heat-resistant liquid, sufficient stirring can make the nanocarbon tubes better dispersed and improve the uniformity of the antistatic, wear-resistant and heat-resistant liquid; then, let it stand for more than 4 hours to achieve the effect of standing to break bubbles and discharge air to obtain each material treatment liquid; then add the mixed liquid of each material treatment liquid to the corresponding coating tank for standby.
[0079] Furthermore, in the step (2), the surface of the first grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400° C., and the time for each high-temperature impurity removal is 30 to 60 minutes. Then, the first grey cloth after impurity removal is subjected to at least two dip coating treatments with a first bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. Then, the first grey cloth after impurity removal is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400° C., and the high-temperature drying time is 30 to 60 minutes. Then, the dried first grey cloth is subjected to two dip coating treatments with a second bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. The heat-resistant bottom layer is subjected to at least two high-temperature drying processes at a temperature of 250 to 350°C for 30 to 60 minutes respectively, and finally, the heat-resistant bottom layer is subjected to at least two high-temperature drying processes at a temperature of 250 to 350°C for 30 to 60 minutes respectively, to obtain a heat-resistant bottom layer, and then the heat-resistant bottom layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dip coating process adopts a dip coating machine; the first grey cloth preferably adopts a glass fiber cloth with a yarn diameter of 9 um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help to improve the cushioning and resilience of the bulked layer. Specifically, after the dip coating process, the weight of the heat-resistant bottom layer is 455 to 470 g / m 2 , and the thickness is 0.3~0.31mm.
[0080] Furthermore, in the step (3), an antistatic, wear-resistant and heat-resistant liquid medicine is uniformly scraped on one side of the second grey cloth, and the scraping thickness is 0.3 to 0.31 mm. Subsequently, a horizontal tunnel oven is used to sequentially dry the second grey cloth at 140°C, 170 to 190°C, 200 to 250°C and 300 to 350°C to obtain a temperature-resistant surface layer, and then the temperature-resistant surface layer is rolled up for standby use, wherein the second grey cloth is dried at 140°C for 3 to 1 0 minutes, dried at 170-190°C for 5-10 minutes, dried at 200-250°C for 30-40 minutes, and dried at 300-350°C for 30-40 minutes; the second grey cloth preferably adopts glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Specifically, after the scraping treatment, the weight of the temperature-resistant surface layer is 455-470g / m 2 , and the thickness is 0.3~0.31mm.
[0081] Further, in the step (4), the surface of the third grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400°C, and the time for each high-temperature impurity removal is 30 to 60 minutes. Secondly, the third grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement liquid, and the dip-coating time is 30 to 60 minutes. Then, the third grey cloth is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. Then, the third grey cloth after drying is subjected to two dip-coating treatments with the buffering and rebound enhancement liquid, and the dip-coating time is 30 to 60 minutes. Then, the third grey cloth is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. The third grey cloth is dried for 30 to 60 minutes, and then the third bonding and reinforcing liquid is used to perform a secondary dip coating treatment on the dried third grey cloth, the dipping time is 30 to 60 minutes respectively, and then at least two high-temperature dryings are performed at a high temperature of 250 to 350°C, the high-temperature drying time is 30 to 60 minutes respectively, to obtain a bulked layer, and then the bulked layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dip coating machine; the third grey cloth preferably adopts a bulked cloth with a yarn diameter of 6um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help to improve the cushioning and resilience of the bulked layer. Specifically, after the dipping treatment, the gram weight of the bulked layer is 1000±15g / m 2 The thickness is 0.85~0.9mm, or the weight is 1390±15g / m 2 The thickness is 1-1.1mm, or the weight is 1690±15g / m 2 And the thickness is 1.35-1.36 mm; if the expanded layer cannot meet the aforementioned weight and thickness requirements, it will affect the bonding strength between the expanded layer and the heat-resistant bottom layer, the heat-resistant surface layer and / or the adhesive layer.
[0082] Furthermore, in step (6), a laminating machine is used to perform high-temperature lamination on the stacked layers of materials, the laminating temperature is 360-400°C, the laminating time is 100-300 seconds, and the laminating pressure is 5-15 kg / cm 2 In addition, it should be noted that during the compounding process, the machine body other than the heating plate needs to be water-cooled to ensure the normal operation of the machine. The water cooling temperature of the machine body is 25-30°C.
[0083] Furthermore, when making the adhesive layer, the surface of the fourth grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400°C, and the time for each high-temperature impurity removal is 30 to 60 minutes. Then, the first grey cloth after impurity removal is subjected to at least two dip coating treatments with the first bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. Then, the fourth grey cloth after drying is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. Then, the fourth grey cloth after drying is subjected to at least two dip coating treatments with the second bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. The time is 30 to 60 minutes respectively, and then at least two high-temperature dryings are carried out at a high temperature of 250 to 350°C, and the high-temperature drying time is 30 to 60 minutes respectively, to obtain an adhesive layer, and then the adhesive layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dip coating treatment adopts a dip coating machine; the fourth grey cloth preferably adopts a glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help to improve the cushioning and resilience of the bulked layer. Specifically, after the dip coating treatment, the gram weight of the adhesive layer is 160 to 170 g / m 2 , and the thickness is 0.09~0.1mm. Specific embodiment 1:
[0085] The present invention discloses a method for processing an antistatic high temperature and high pressure resistant polymer cushion, wherein the polymer cushion comprises only one temperature resistant bottom layer, only one temperature resistant surface layer, and only one expanded layer disposed between the temperature resistant surface layer and the temperature resistant bottom layer. The processing steps of the polymer cushion are as follows:
[0086] First, according to the potion formula components required for material treatment of the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer, raw materials are respectively measured and prepared to obtain several material treatment potions, and various material treatment potions are respectively added to the processing equipment of the corresponding layer materials for standby use, wherein the material treatment potions include antistatic wear-resistant and heat-resistant potions, first bonding enhancement potions, second bonding enhancement potions, third bonding enhancement potions and buffering and rebound enhancement potions;
[0087] The antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight:
[0088] Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%;
[0089] The first binding enhancement liquid contains the following components by weight:
[0090] Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%;
[0091] The second binding enhancement liquid contains the following components by weight:
[0092] Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%;
[0093] The third binding enhancement liquid contains the following components by weight:
[0094] Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%;
[0095] The buffering and rebound enhancing liquid contains the following components by weight:
[0096] Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%.
[0097] Among them, it should be noted that the material treatment liquids of the antistatic, wear-resistant and heat-resistant liquid, the first bonding enhancement liquid, the second bonding enhancement liquid, the third bonding enhancement liquid and the buffering and rebound enhancement liquid, after taking each raw material according to the weight of each material treatment liquid, need to be stirred and mixed at high speed in a blender for 30 to 60 minutes, and the stirring speed is 1200 to 1450r / min, so that the raw materials of each material treatment liquid are fully stirred to improve the dispersion uniformity; especially the antistatic, wear-resistant and heat-resistant liquid, sufficient stirring can make the nanocarbon tubes better dispersed and improve the uniformity of the antistatic, wear-resistant and heat-resistant liquid; then, let it stand for more than 4 hours to achieve the effect of standing to break bubbles and discharge air to obtain each material treatment liquid; then add the mixed liquid of each material treatment liquid to the corresponding coating tank for standby.
[0098] Secondly, take the first grey cloth, which is preferably made of glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulk layer. Subsequently, the surface of the first grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and the time for each high-temperature impurity removal is 30-60 minutes. Then, the first bonding enhancement solution is used to perform at least two dip-coating treatments on the first grey cloth after impurity removal, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are performed at a high temperature of 300-400°C. , high temperature drying time is 30 to 60 minutes respectively, then, the dried first grey cloth is dipped for a second time with the second bonding enhancement liquid, the dipping time is 30 to 60 minutes respectively, finally, at least two high temperature dryings are carried out at a high temperature of 250 to 350°C, the high temperature drying time is 30 to 60 minutes respectively, to obtain a heat-resistant bottom layer, and then the heat-resistant bottom layer is rolled up for standby use, wherein the high temperature impurity removal or high temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dipping machine; after the dipping treatment, the gram weight of the obtained heat-resistant bottom layer is 455 to 470 g / m 2 , and the thickness is 0.3~0.31mm.
[0099] Next, take the second grey cloth. The second grey cloth preferably adopts glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Then, use antistatic, wear-resistant and heat-resistant liquid medicine to evenly scrape on one side of the second grey cloth. The scraping thickness is 0.3-0.31mm. Then, use a horizontal tunnel oven to heat the second grey cloth in a segmented manner at 140℃, 170-190℃, 200℃-250℃ in sequence. and 300℃~350℃ temperature to obtain a heat-resistant surface layer, and then the heat-resistant surface layer is rolled up for standby use, wherein the heat-resistant surface layer is dried at 140℃ for 3~10 minutes, at 170~190℃ for 5~10 minutes, at 200℃~250℃ for 30~40 minutes, and at 300℃~350℃ for 30~40 minutes to obtain a heat-resistant surface layer for standby use; after the scraping treatment, the gram weight of the heat-resistant surface layer obtained is 455~470g / m 2 , and the thickness is 0.3~0.31mm;
[0100] Further, a third grey cloth is taken, and the third grey cloth is preferably a bulked cloth with a yarn diameter of 6um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Subsequently, the surface of the third grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and each high-temperature impurity removal time is 30-60 minutes. Secondly, the third grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement liquid, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are carried out at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes. Then, the dried third grey cloth is subjected to a buffering and rebound enhancement liquid. The third cloth is subjected to a secondary dip coating treatment, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. Then, the dried third cloth is subjected to a secondary dip coating treatment using a third bonding enhancement solution, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 250 to 350°C, and the high-temperature drying time is 30 to 60 minutes to obtain an expanded layer, and then the expanded layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dip coating treatment adopts a dip coating machine; after the dip coating treatment, the gram weight of the expanded layer obtained is 1000±15g / m 2 The thickness is 0.85~0.9mm, or the weight is 1390±15g / m 2 The thickness is 1-1.1mm, or the weight is 1690±15g / m 2 And the thickness is 1.35-1.36 mm; if the expanded layer cannot meet the aforementioned weight and thickness requirements, it will affect the bonding strength between the expanded layer and the heat-resistant bottom layer, the heat-resistant surface layer and / or the adhesive layer.
[0101] Furthermore, the rolls of the heat-resistant bottom layer, the heat-resistant surface layer, and the expanded layer prepared above are respectively arranged at the discharge end of the compounding machine, and the heat-resistant bottom layer, the heat-resistant surface layer, and the expanded layer are aligned and stacked according to the structural order of the polymer cushion. Subsequently, one end of each stacked layer of material is passed through the compounding part of the compounding machine through the first traction part at one end of the compounding machine, and is pre-installed on the second traction part at the other end of the compounding machine;
[0102] Then, the processing equipment is started, and the first traction part and the second traction part respectively arranged at the two ends of the compounding machine are used to pull the aforementioned superimposed layers of materials from the feeding end of the compounding part to the processing area of the compounding part for high-temperature compounding. The compounding temperature is 360-400°C, the compounding time is 100-300 seconds, and the compounding pressure is 5-15kg / cm 2, obtain a strip-shaped polymer cushioning material. In addition, it should be noted that during the compounding operation, the compounding machine body other than the heating plate needs to be water-cooled to ensure the normal operation of the compounding machine. The water cooling temperature of the body is: 25-30°C.
[0103] Finally, the processing equipment transports the aforementioned obtained polymer cushioning material to a cutting section of the processing equipment in a fixed length through a second traction section, and the polymer cushioning material is cut through the cutting section to obtain a polymer cushioning pad. Specific embodiment 2:
[0105] The present invention discloses a processing method of an antistatic high temperature and high pressure resistant polymer cushion, wherein the polymer cushion comprises one and only one temperature resistant bottom layer, one and only one temperature resistant surface layer, two or more expanded layers arranged between the temperature resistant surface layer and the temperature resistant bottom layer, and one and only one bonding layer arranged between the expanded layers. The processing steps of the polymer cushion are as follows:
[0106] First, according to the potion formula components required for material treatment of the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer and the bonding layer, raw materials are respectively measured and prepared to obtain several material treatment potions, and various material treatment potions are respectively added to the processing equipment of the corresponding layer materials for standby use, wherein the material treatment potions include antistatic wear-resistant and heat-resistant potions, first bonding enhancement potions, second bonding enhancement potions, third bonding enhancement potions and buffering and rebound enhancement potions;
[0107] The antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight:
[0108] Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%;
[0109] The first binding enhancement liquid contains the following components by weight:
[0110] Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%;
[0111] The second binding enhancement liquid contains the following components by weight:
[0112] Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%;
[0113] The third binding enhancement liquid contains the following components by weight:
[0114] Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%;
[0115] The buffering and rebound enhancing liquid contains the following components by weight:
[0116] Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%.
[0117] Among them, it should be noted that the material treatment liquids of the antistatic, wear-resistant and heat-resistant liquid, the first bonding enhancement liquid, the second bonding enhancement liquid, the third bonding enhancement liquid and the buffering and rebound enhancement liquid, after taking each raw material according to the weight of each material treatment liquid, need to be stirred and mixed at high speed in a blender for 30 to 60 minutes, and the stirring speed is 1200 to 1450r / min, so that the raw materials of each material treatment liquid are fully stirred to improve the dispersion uniformity; especially the antistatic, wear-resistant and heat-resistant liquid, sufficient stirring can make the nanocarbon tubes better dispersed and improve the uniformity of the antistatic, wear-resistant and heat-resistant liquid; then, let it stand for more than 4 hours to achieve the effect of standing to break bubbles and discharge air to obtain each material treatment liquid; then add the mixed liquid of each material treatment liquid to the corresponding coating tank for standby.
[0118] Secondly, take the first grey cloth, which is preferably made of glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulk layer. Subsequently, the surface of the first grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and the time for each high-temperature impurity removal is 30-60 minutes. Then, the first bonding enhancement solution is used to perform at least two dip-coating treatments on the first grey cloth after impurity removal, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are performed at a high temperature of 300-400°C. , high temperature drying time is 30 to 60 minutes respectively, then, the dried first grey cloth is dipped for a second time with the second bonding enhancement liquid, the dipping time is 30 to 60 minutes respectively, finally, at least two high temperature dryings are carried out at a high temperature of 250 to 350°C, the high temperature drying time is 30 to 60 minutes respectively, to obtain a heat-resistant bottom layer, and then the heat-resistant bottom layer is rolled up for standby use, wherein the high temperature impurity removal or high temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dipping machine; after the dipping treatment, the gram weight of the obtained heat-resistant bottom layer is 455 to 470 g / m 2 , and the thickness is 0.3~0.31mm.
[0119] Next, take the second grey cloth. The second grey cloth preferably adopts glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Then, use antistatic, wear-resistant and heat-resistant liquid medicine to evenly scrape on one side of the second grey cloth. The scraping thickness is 0.3-0.31mm. Then, use a horizontal tunnel oven to heat the second grey cloth in a segmented manner at 140℃, 170-190℃, 200℃-250℃ in sequence. and 300℃~350℃ temperature to obtain a heat-resistant surface layer, and then the heat-resistant surface layer is rolled up for standby use, wherein the heat-resistant surface layer is dried at 140℃ for 3~10 minutes, at 170~190℃ for 5~10 minutes, at 200℃~250℃ for 30~40 minutes, and at 300℃~350℃ for 30~40 minutes to obtain a heat-resistant surface layer for standby use; after the scraping treatment, the gram weight of the heat-resistant surface layer obtained is 455~470g / m 2 , and the thickness is 0.3~0.31mm;
[0120] Further, a third grey cloth is taken, and the third grey cloth is preferably a bulked cloth with a yarn diameter of 6um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Subsequently, the surface of the third grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and each high-temperature impurity removal time is 30-60 minutes. Secondly, the third grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement liquid, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are carried out at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes. Then, the dried third grey cloth is subjected to a buffering and rebound enhancement liquid. The third cloth is subjected to a secondary dip coating treatment, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. Then, the dried third cloth is subjected to a secondary dip coating treatment using a third bonding enhancement solution, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 250 to 350°C, and the high-temperature drying time is 30 to 60 minutes to obtain an expanded layer, and then the expanded layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dip coating treatment adopts a dip coating machine; after the dip coating treatment, the gram weight of the expanded layer obtained is 1000±15g / m 2 The thickness is 0.85~0.9mm, or the weight is 1390±15g / m 2 The thickness is 1-1.1mm, or the weight is 1690±15g / m 2And the thickness is 1.35-1.36 mm; if the expanded layer cannot meet the aforementioned weight and thickness requirements, it will affect the bonding strength between the expanded layer and the heat-resistant bottom layer, the heat-resistant surface layer and / or the adhesive layer.
[0121] Further, a fourth grey cloth is taken, and the fourth grey cloth is preferably made of glass fiber cloth with a yarn diameter of 9 um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Subsequently, the surface of the fourth grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400°C, and the time for each high-temperature impurity removal is 30 to 60 minutes. Secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement solution, and the dip-coating time is 30 to 60 minutes. At least two high-temperature dryings are performed at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes respectively. Then, the fourth grey cloth after drying is dipped at least twice with the second bonding enhancement liquid, and the dipping time is 30-60 minutes respectively. Then, at least two high-temperature dryings are performed at a high temperature of 250-350°C, and the high-temperature drying time is 30-60 minutes respectively, to obtain an adhesive layer, which is then rolled up for standby use. After the dip-coating treatment, the gram weight of the adhesive layer obtained is 160-170 g / m 2 , and the thickness is 0.09~0.1mm.
[0122] Furthermore, the rolls of the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer, and the adhesive layer prepared above are respectively arranged at the discharge end of the compounding machine, and the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer, and the adhesive layer are aligned and stacked according to the structural order of the polymer cushion. Subsequently, one end of each stacked layer of material is passed through the compounding part of the compounding machine through the first traction part at one end of the compounding machine, and is pre-installed on the second traction part at the other end of the compounding machine;
[0123] Then, the processing equipment is started, and the first traction part and the second traction part respectively arranged at the two ends of the compounding machine are used to pull the aforementioned superimposed layers of materials from the feeding end of the compounding part to the processing area of the compounding part for high-temperature compounding. The compounding temperature is 360-400°C, the compounding time is 100-300 seconds, and the compounding pressure is 5-15kg / cm 2 , obtain a strip-shaped polymer cushioning material. In addition, it should be noted that during the compounding operation, the compounding machine body other than the heating plate needs to be water-cooled to ensure the normal operation of the compounding machine. The water cooling temperature of the body is: 25-30°C.
[0124] Finally, the processing equipment transports the aforementioned obtained polymer cushioning material to a cutting section of the processing equipment in a fixed length through a second traction section, and the polymer cushioning material is cut through the cutting section to obtain a polymer cushioning pad. Specific embodiment 3:
[0126] The present invention discloses a method for processing an antistatic high temperature and high pressure resistant polymer cushion, wherein the polymer cushion comprises two or more heat resistant bottom layers, two or more heat resistant surface layers, and the heat resistant surface layers are arranged on opposite sides and closest to each other, two expanded layers are arranged between the heat resistant bottom layers, and at least two adhesive layers are arranged between the two expanded layers. The processing steps of the polymer cushion are as follows:
[0127] First, according to the potion formula components required for material treatment of the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer and the bonding layer, raw materials are respectively measured and prepared to obtain several material treatment potions, and various material treatment potions are respectively added to the processing equipment of the corresponding layer materials for standby use, wherein the material treatment potions include antistatic wear-resistant and heat-resistant potions, first bonding enhancement potions, second bonding enhancement potions, third bonding enhancement potions and buffering and rebound enhancement potions;
[0128] The antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight:
[0129] Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%;
[0130] The first binding enhancement liquid contains the following components by weight:
[0131] Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%;
[0132] The second binding enhancement liquid contains the following components by weight:
[0133] Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%;
[0134] The third binding enhancement liquid contains the following components by weight:
[0135] Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%;
[0136] The buffering and rebound enhancing liquid contains the following components by weight:
[0137] Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%.
[0138] Among them, it should be noted that the material treatment liquids of the antistatic, wear-resistant and heat-resistant liquid, the first bonding enhancement liquid, the second bonding enhancement liquid, the third bonding enhancement liquid and the buffering and rebound enhancement liquid, after taking each raw material according to the weight of each material treatment liquid, need to be stirred and mixed at high speed in a blender for 30 to 60 minutes, and the stirring speed is 1200 to 1450r / min, so that the raw materials of each material treatment liquid are fully stirred to improve the dispersion uniformity; especially the antistatic, wear-resistant and heat-resistant liquid, sufficient stirring can make the nanocarbon tubes better dispersed and improve the uniformity of the antistatic, wear-resistant and heat-resistant liquid; then, let it stand for more than 4 hours to achieve the effect of standing to break bubbles and discharge air to obtain each material treatment liquid; then add the mixed liquid of each material treatment liquid to the corresponding coating tank for standby.
[0139] Secondly, take the first grey cloth, which is preferably made of glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulk layer. Subsequently, the surface of the first grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and the time for each high-temperature impurity removal is 30-60 minutes. Then, the first bonding enhancement solution is used to perform at least two dip-coating treatments on the first grey cloth after impurity removal, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are performed at a high temperature of 300-400°C. , high temperature drying time is 30 to 60 minutes respectively, then, the dried first grey cloth is dipped for a second time with the second bonding enhancement liquid, the dipping time is 30 to 60 minutes respectively, finally, at least two high temperature dryings are carried out at a high temperature of 250 to 350°C, the high temperature drying time is 30 to 60 minutes respectively, to obtain a heat-resistant bottom layer, and then the heat-resistant bottom layer is rolled up for standby use, wherein the high temperature impurity removal or high temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dipping machine; after the dipping treatment, the gram weight of the obtained heat-resistant bottom layer is 455 to 470 g / m 2 , and the thickness is 0.3~0.31mm.
[0140] Next, take the second grey cloth. The second grey cloth preferably adopts glass fiber cloth with a yarn diameter of 9um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Then, use antistatic, wear-resistant and heat-resistant liquid medicine to evenly scrape on one side of the second grey cloth. The scraping thickness is 0.3-0.31mm. Then, use a horizontal tunnel oven to heat the second grey cloth in a segmented manner at 140℃, 170-190℃, 200℃-250℃ in sequence. and 300℃~350℃ temperature to obtain a heat-resistant surface layer, and then the heat-resistant surface layer is rolled up for standby use, wherein the heat-resistant surface layer is dried at 140℃ for 3~10 minutes, at 170~190℃ for 5~10 minutes, at 200℃~250℃ for 30~40 minutes, and at 300℃~350℃ for 30~40 minutes to obtain a heat-resistant surface layer for standby use; after the scraping treatment, the gram weight of the heat-resistant surface layer obtained is 455~470g / m 2 , and the thickness is 0.3~0.31mm;
[0141] Further, a third grey cloth is taken, and the third grey cloth is preferably a bulked cloth with a yarn diameter of 6um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Subsequently, the surface of the third grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and each high-temperature impurity removal time is 30-60 minutes. Secondly, the third grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement liquid, and the dip-coating time is 30-60 minutes. Then, at least two high-temperature dryings are carried out at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes. Then, the dried third grey cloth is subjected to a buffering and rebound enhancement liquid. The third cloth is subjected to a secondary dip coating treatment, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 300 to 400°C, and the high-temperature drying time is 30 to 60 minutes. Then, the dried third cloth is subjected to a secondary dip coating treatment using a third bonding enhancement solution, the dipping time is 30 to 60 minutes, and then at least a secondary high-temperature drying is carried out at a high temperature of 250 to 350°C, and the high-temperature drying time is 30 to 60 minutes to obtain an expanded layer, and then the expanded layer is rolled up for standby use; wherein, the high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace; the dip coating treatment adopts a dip coating machine; after the dip coating treatment, the gram weight of the expanded layer obtained is 1000±15g / m 2 The thickness is 0.85~0.9mm, or the weight is 1390±15g / m 2 The thickness is 1-1.1mm, or the weight is 1690±15g / m 2And the thickness is 1.35-1.36 mm; if the expanded layer cannot meet the aforementioned weight and thickness requirements, it will affect the bonding strength between the expanded layer and the heat-resistant bottom layer, the heat-resistant surface layer and / or the adhesive layer.
[0142] Further, a fourth grey cloth is taken, and the fourth grey cloth is preferably made of glass fiber cloth with a yarn diameter of 9 um. The finer the yarn diameter of the glass fiber cloth, the better the softness, which can help improve the cushioning and resilience of the bulked layer. Subsequently, the surface of the fourth grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400°C, and the time for each high-temperature impurity removal is 30 to 60 minutes. Secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with the first bonding enhancement solution, and the dip-coating time is 30 to 60 minutes. At least two high-temperature dryings are performed at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes respectively. Then, the fourth grey cloth after drying is dipped at least twice with the second bonding enhancement liquid, and the dipping time is 30-60 minutes respectively. Then, at least two high-temperature dryings are performed at a high temperature of 250-350°C, and the high-temperature drying time is 30-60 minutes respectively, to obtain an adhesive layer, which is then rolled up for standby use. After the dip-coating treatment, the gram weight of the adhesive layer obtained is 160-170 g / m 2 , and the thickness is 0.09~0.1mm.
[0143] Furthermore, the rolls of the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer, and the adhesive layer prepared above are respectively arranged at the discharge end of the compounding machine, and the heat-resistant bottom layer, the heat-resistant surface layer, the expanded layer, and the adhesive layer are aligned and stacked according to the structural order of the polymer cushion. Subsequently, one end of each stacked layer of material is passed through the compounding part of the compounding machine through the first traction part at one end of the compounding machine, and is pre-installed on the second traction part at the other end of the compounding machine;
[0144] Then, the processing equipment is started, and the first traction part and the second traction part respectively arranged at the two ends of the compounding machine are used to pull the aforementioned superimposed layers of materials from the feeding end of the compounding part to the processing area of the compounding part for high-temperature compounding. The compounding temperature is 360-400°C, the compounding time is 100-300 seconds, and the compounding pressure is 5-15kg / cm 2 , obtain a strip-shaped polymer cushioning material. In addition, it should be noted that during the compounding operation, the compounding machine body other than the heating plate needs to be water-cooled to ensure the normal operation of the compounding machine. The water cooling temperature of the body is: 25-30°C.
[0145] Finally, the processing equipment transports the aforementioned obtained polymer cushioning material to a cutting section of the processing equipment in a fixed length through a second traction section, and the polymer cushioning material is cut through the cutting section to obtain a polymer cushioning pad.
[0146] In addition, it should be noted that the weight measurement of the heat-resistant base layer, heat-resistant surface layer, expanded layer and adhesive layer is determined by using a balance, and the thickness measurement of the heat-resistant base layer, heat-resistant surface layer, expanded layer and adhesive layer is determined by using a micrometer.
[0147] The polymer cushion prepared by the present invention is sampled, and the sampling size is 780×1295 mm; the sample is placed on a press to perform a life test: the polymer cushion is pressurized to 25 kg / cm 2 The pressing temperature is 220℃, the heating time is 120 minutes, the cooling time is 30 minutes, and the opening time is 5 minutes. If the operation is carried out in this way, the pressing is performed 1000 times. The polymer cushion has no obvious change after being used for 800 times, which can meet the production needs.
[0148] Secondly, after the product is placed in the PCB lamination vacuum high temperature press, the automatic suction and adjustment machine takes the upper cover plate to confirm that the buffer pad can be quickly separated from the upper cover plate, and the automatic suction and adjustment machine takes off the polymer buffer pad to confirm that the buffer pad can be quickly separated from the lower steel plate.
[0149] Next, the polymer cushion was compared with the coating heat resistance. The polymer cushion was placed in a PCB pressing vacuum high-temperature press, and the parameters were set to 380 degrees for 4 hours, a pressure of 420psi, and a vacuum degree of 730±30mmHg. After pressing, it was confirmed that the surface material had no decomposition, severe discoloration or aging.
[0150] Furthermore, the product was cut into a size of 60×230㎜, a friction area of 50×200㎜, and placed on the wear tester. The number of times was set to 1000 times, the friction speed was 21r / min, the friction load was 4LB, and the sandpaper model was 1200cw. After the test, it was confirmed that there was no cloth texture and serious dust on the surface coating.
[0151] Subsequently, a surface measuring instrument was placed on the surface coating of the polymer cushion pad, and the test resistance was 106 = 1 megohm, while the standard is less than 108, meeting the anti-static requirements.
[0152] In summary, the service life of the polymer cushion prepared by the present invention is 500 times better than that of the fluororubber coating; the temperature resistance is 260-380°C, which is better than that of the fluororubber coating at 250°C; the cushioning and rebound properties are better than those of the fluororubber coating after long-term aging use; the heating rate is equivalent to that of the kraft paper originally used, which meets the production requirements; the thickness change is less than 0.3mm, and the dimensional stability change is <50um.
[0153] Specifically, when testing the cushioning capacity of the polymer cushion prepared by the present invention, two samples of 10×15 cm in size are taken, and a common lead strip is selected, which is 1 mm thicker than the polymer cushion. The cut cushion and lead strip are placed on the hot plate of the press, and then the pressure is gradually increased to 40 kg / cm 2 , the pressing temperature is 220℃, the heating time is 60 minutes, and the cold pressing time is 20 minutes; after reaching the test time, the change in the thickness of the lead strip is measured, which is the buffer amount, and the number of pressing times for physical property confirmation is 1 time, 100 times, 200 times... every 100 times; the test principle, such as Figure 3 As shown, the test results, such as Figure 4 , 5 As shown, according to the test data, the polymer cushioning pad prepared by the present invention can maintain a cushioning capacity of more than 0.4-0.7 mm after being used 800 times, and the cushioning capacity can meet the production demand.
[0154] Furthermore, when the polymer cushion pad prepared by the present invention is tested for the heating rate, a size of 1143×1295 mm is taken, and a press is used. Kraft paper, general cushion pad, foreign well-known brand cushion pad and the polymer cushion pad prepared by the present invention are respectively used, and the material temperature lines are connected respectively to test the heating rates of the three products. The press uses a fixed program 4A-50, the temperature is 190°C, the hot pressing time is 130 minutes, the pressure reduction time is 30 minutes, and the open time is 5 minutes; confirm that the number of pressing times increases: 1 time, 50 times, 100 times, and after each increase of 100 times, the heating rate is measured. The test results are: the heating rate of the polymer cushion pads prepared by foreign well-known brands and the present invention is 0.2°C / min faster than that of kraft paper, which is within the standard range, and remains consistent in the later period. Figure 6 shown.
[0155] Moreover, the general cushion pad cannot meet the heating rate requirement after 200 times of use, the kraft paper cannot meet the production after 6 times of use, the heating rate of the well-known foreign brand cushion pad is between 1.9 and 2.1 ° C / min after 500 times of use, and the polymer cushion pad prepared by the present invention uses the same pressing procedure, and the heating rate is between 2.1 and 2.2 ° C / min after 800 times of pressing. Figure 7 shown.
[0156] Furthermore, the polymer cushion was tested for thickness change and dimensional stability change. The sample size was 600×600 mm and the pressure was increased to 40 kg / cm by a press. 2The pressing temperature is 220°C, the heating time is 120 minutes, the cooling time is 30 minutes, the opening time is 5 minutes, and the thickness change data is recorded once, 50 times, and every 100 times. At the same time, under the same test conditions, the "general buffer pad", "12 sheets of kraft paper", "16 sheets of kraft paper" and "buffer pad of a well-known foreign brand" are tested respectively. The test results are as follows: the thickness change of the general buffer pad after 200 times of pressing obviously exceeds the 0.5mm tolerance, the thickness of the kraft paper changes significantly after being reused for 6 times, the foreign well-known buffer pad can meet the use of 500 times with little change, the buffer pad prepared by the present invention has a very small thickness change of about 0.3mm when pressed 800 times, and the thickness change of the buffer pad prepared by the present invention is better than that of the foreign well-known buffer pad, the general buffer pad and the kraft paper, such as Figure 8 shown.
[0157] Moreover, the expansion and contraction data of the general cushion pad exceeds the control standard by 50um after 200 uses, and the kraft paper cannot meet the production after 6 times of production. The cushion pad made by the present invention has an expansion and contraction value within 50um after 800 times of pressing, which is within the controllable range. The cushion pad made by the present invention has better expansion and contraction stability than the general cushion pad and kraft paper. Fig. 9 shown.
[0158] The above description is only a preferred embodiment of the present invention and does not limit the scope of the present invention. Therefore, without departing from the design spirit of the present invention, the equivalent changes or decorations made by ordinary engineers and technicians in this field to the structure, method, characteristics and principles described in the present invention should fall within the protection scope of the patent application of the present invention.
Claims
1. A method for processing an antistatic, high temperature and high pressure resistant polymer cushion, characterized in that: The polymer cushion comprises at least one heat-resistant bottom layer, at least one heat-resistant surface layer, and at least one expanded layer disposed between the heat-resistant surface layer and the heat-resistant bottom layer. When there are two or more expanded layers, each expanded layer is connected by at least one adhesive layer. The processing steps of the polymer cushion are as follows: (1) Preparation of medicine: according to the formula components of the medicine required for the material treatment of the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer, the raw materials are respectively measured and prepared to obtain several kinds of material treatment medicines, and various material treatment medicines are respectively added to the processing equipment of the corresponding layer materials for standby use. When the expanded layer has more than two layers, the material treatment medicine is prepared according to the formula components of the medicine required for the material treatment of the adhesive layer for standby use; The material treatment solution in step (1) includes an antistatic, wear-resistant and heat-resistant solution, a first bonding enhancement solution, a second bonding enhancement solution, a third bonding enhancement solution and a buffering and rebound enhancement solution; The antistatic, wear-resistant and heat-resistant liquid medicine comprises the following components by weight: Polyimide: 89.7±5%, carbon nanotubes: 10±5%, glass beads: 0.3±5%; The first binding enhancement liquid contains the following components by weight: Pure water: 60-85%, PTFE dispersion: 10-30%, silane coupling agent: 5-10%; The second binding enhancement liquid contains the following components by weight: Pure water: 40-65%, PTFE dispersion: 15-20%, PFA: 10-20%, FEP: 10-20%; The third binding enhancement liquid contains the following components by weight: Pure water: 70-79%, PTFE dispersion: 15-20%, PFA: 3-5%, FEP: 3-5%; The buffering and rebound enhancing liquid contains the following components by weight: Pure water: 70-79%, PTFE dispersion: 15-20%, white carbon black: 3-5%, SiO2: 3-5%; (2) preparing a heat-resistant bottom layer: taking a first grey cloth, performing a surface high-temperature pretreatment on the first grey cloth, and then using the first bonding enhancement solution and the second bonding enhancement solution in step (1) to dip-coat the first grey cloth respectively, performing a heating treatment after each dipping treatment, and then rolling up to obtain a heat-resistant bottom layer for standby use; (3) preparing a heat-resistant surface layer: taking a second grey cloth, applying the antistatic, wear-resistant and heat-resistant liquid medicine in step (1) to at least one side of the second grey cloth by scraping, and then drying and rolling the second grey cloth by a staged heating method to obtain a heat-resistant surface layer for later use; (4) Making a bulked layer: taking a third grey cloth, performing a surface high temperature pretreatment on the third grey cloth, and then using the first bonding enhancement solution, the buffering and rebound enhancement solution, and the third bonding enhancement solution in step (1) to dip-coat the third grey cloth respectively, performing a heating treatment after each dipping treatment, and then rolling up to obtain a bulked layer for standby use; (5) Material roll packing machine: the material rolls of the heat-resistant bottom layer of step (2), the heat-resistant surface layer of step (3), and the expanded layer of step (4) are respectively arranged at the unloading end of the equipment, and the heat-resistant bottom layer, the heat-resistant surface layer and the expanded layer are aligned and stacked according to the structural order of the polymer cushion. When the expanded layer is two or more layers, at least one adhesive layer is arranged at the unloading end, and the adhesive layer is arranged between the two expanded layers. Subsequently, one end of each stacked layer of material passes through the composite part of the processing equipment through the first traction part of the processing equipment, and is pre-installed on the second traction part of the processing equipment; (6) Material compounding: starting the processing equipment, and using the first traction part and the second traction part of the processing equipment to pull the layers of materials stacked in step (5) from the feed end of the compounding part to the processing area of the compounding part at a fixed length, and perform high-temperature compounding to obtain a strip-shaped polymer buffer material; (7) Material cutting: The processing equipment transports the polymer cushioning material of step (6) to the cutting part of the processing equipment at a fixed length through the second traction part, and the polymer cushioning material is cut by the cutting part to obtain a polymer cushioning pad; When the expanded layer has two or more layers, an adhesive layer is prepared: a fourth grey cloth is taken, the surface of the fourth grey cloth is subjected to high-temperature pretreatment, and then the fourth grey cloth is dipped in the first bonding enhancement solution and the second bonding enhancement solution in step (1), respectively, and after each dipping treatment, a heating treatment is performed, and then the fourth grey cloth is rolled up to obtain an adhesive layer.
2. The processing method of the antistatic high temperature and high pressure resistant polymer cushion according to claim 1 is characterized in that: The antistatic, wear-resistant and heat-resistant potion, the first bonding enhancement potion, the second bonding enhancement potion, the third bonding enhancement potion and the buffering and rebound enhancement potion are respectively taken according to the weight proportion of each material treatment potion, mixed at high speed in a blender for 30 to 60 minutes at a stirring speed of 1200 to 1450 r / min, and then left to stand for more than 4 hours to obtain the obtained product.
3. The processing method of the antistatic high temperature and high pressure resistant polymer cushion according to claim 1 is characterized in that: In the step (2), the surface of the first grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, each high-temperature impurity removal time is 30-60 minutes. Secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with a first bonding enhancement liquid, each dip-coating time is 30-60 minutes. Next, at least two high-temperature dryings are performed at a high temperature of 300-400°C, each high-temperature drying time is 30-60 minutes. Then, the dried first grey cloth is subjected to two dip-coating treatments with a second bonding enhancement liquid, each dip-coating time is 30-60 minutes. Finally, at least two high-temperature dryings are performed at a high temperature of 250-350°C, each high-temperature drying time is 30-60 minutes, to obtain a heat-resistant bottom layer, which is then rolled up for standby use. The high-temperature impurity removal or high-temperature drying is performed using a vertical tunnel furnace, and the dip-coating treatment is performed using a dip coater.
4. The processing method of the antistatic high temperature and high pressure resistant polymer cushion according to claim 1 is characterized in that: In the step (3), an antistatic, wear-resistant and heat-resistant liquid medicine is uniformly scraped on one side of the second grey cloth, and the scraping thickness is 0.3-0.31 mm. Subsequently, the second grey cloth is dried at 140°C, 170-190°C, 200°C-250°C and 300°C-350°C in sequence to obtain a temperature-resistant surface layer, and then the temperature-resistant surface layer is rolled up for standby use, wherein the drying is performed at 140°C for 3-10 minutes, at 170-190°C for 5-10 minutes, at 200°C-250°C for 30-40 minutes, and at 300°C-350°C for 30-40 minutes.
5. The processing method of the antistatic high temperature and high pressure resistant polymer cushion according to claim 1, characterized in that: In the step (4), the surface of the third grey cloth is first subjected to at least two high-temperature impurity removal treatments at a high temperature of 300 to 400° C., and the time for each high-temperature impurity removal is 30 to 60 minutes. Then, the third grey cloth after impurity removal is subjected to at least two dip coating treatments with the first bonding enhancement liquid, and the dip coating time is 30 to 60 minutes. Then, the third grey cloth after impurity removal is subjected to at least two high-temperature drying treatments at a high temperature of 300 to 400° C., and the high-temperature drying time is 30 to 60 minutes. Then, the third grey cloth after drying is subjected to two dip coating treatments with the buffering rebound enhancement liquid, and the dip coating time is 30 to 60 minutes. The method comprises the following steps: first, drying the third grey cloth for a second time at a temperature of 0 to 60 minutes, and then drying it at a high temperature of 300 to 400°C for at least two times, the time of high temperature drying is 30 to 60 minutes respectively; then, the third grey cloth after drying is dipped for a second time with a third bonding strengthening liquid, the time of dipping is 30 to 60 minutes respectively; then, drying it at a high temperature of 250 to 350°C for at least two times, the time of high temperature drying is 30 to 60 minutes respectively, to obtain a bulked layer, and then the bulked layer is rolled up for standby use; wherein, the high temperature impurity removal or high temperature drying adopts a vertical tunnel furnace; the dipping treatment adopts a dip coater.
6. The method for processing the antistatic high temperature and high pressure resistant polymer cushion according to claim 1, characterized in that: In the step (6), a laminating machine is used to perform high-temperature lamination on the stacked layers of materials. The laminating temperature is 360-400°C, the laminating time is 100-300 seconds, and the laminating pressure is 5-15 kg / cm 2 .
7. The method for processing the antistatic high temperature and high pressure resistant polymer cushion according to claim 1, characterized in that: When making the bonding layer, firstly, the surface of the fourth grey cloth is subjected to at least two high-temperature impurity removal treatments at a high temperature of 300-400°C, and each high-temperature impurity removal time is 30-60 minutes respectively. Secondly, the first grey cloth after impurity removal is subjected to at least two dip-coating treatments with a first bonding enhancement liquid, and the dip-coating time is 30-60 minutes respectively. Then, the first grey cloth is subjected to at least two high-temperature drying at a high temperature of 300-400°C, and the high-temperature drying time is 30-60 minutes respectively. Then, the fourth grey cloth after drying is subjected to at least two dip-coating treatments with a second bonding enhancement liquid, and the dip-coating time is 30-60 minutes respectively. Then, the fourth grey cloth is subjected to at least two high-temperature drying at a high temperature of 250-350°C, and the high-temperature drying time is 30-60 minutes respectively. The bonding layer is then rolled up for standby use. The high-temperature impurity removal or high-temperature drying adopts a vertical tunnel furnace, and the dip-coating treatment adopts a dip coater.
Citation Information
Patent Citations
Printed circuit board laminating cushion and preparation method thereof
CN108790309A
Antistatic cushion for printed circuit board and preparation method of antistatic cushion
CN110370776A